Peran Mediasi Komitmen Organisasional pada Pengaruh Kompetensi dan Self-Efficacy Terhadap Kinerja Pegawai : Studi pada PT. BPR BKK Purwokerto (Perseroda) - Turmini Turmini; Suhana Suhana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of competence and self-efficacy on employee performance at PT BPR BKK Purwokerto (Perseroda) directly and through the mediation of organizational commitment. In addition, this study also examines the influence of organizational commitment on employee performance. This study uses a quantitative approach with primary data. The research sample includes employees in the marketing and supervisory departments of PT BPR BKK Purwokerto (Perseroda) with a total sample of 127 respondents. The data collection technique uses a questionnaire with a five-point Likert scale that measures the variables of competence, self-efficacy, organizational commitment, and performance. Data analysis uses validity tests, reliability tests, multiple linear regression analysis, and the Sobel test using the SPSS application. The results of the study indicate that competence, self-efficacy, and organizational commitment have a significant positive effect on performance. The results also show that competence and self-efficacy have a positive and significant effect on organizational commitment. The results of this study also indicate that organizational commitment acts as a mediator in the influence of competence and self-efficacy on performance. The theoretical implication of this study is to add empirical studies related to the relationship between the variables in this study. The results of this study are expected to provide input for PT BPR BKK Purwokerto (Perseroda) in determining policies and improving employee performance. This study has limitations and suggests future research.